Green Synthesis of Gold and Iron Nanoparticles for Targeted Delivery: An In Vitro and In Vivo Study. (23rd November 2021) - Khanzada, Beenish; Akthar, Nosheen; Bhatti, Muhammad Zeeshan; Ismail, Hammad; Alqarni, Mohammed; Mirza, Bushra; Mostafa-Hedeab, Gomaa; Batiha, Gaber El-Saber
Abstract : Nanotechnology has vast applications in almost all fields of science and technology. The use of medicinal plants for the synthesis of metallic nanoparticles has gained much attention nowadays. In the current research work, six medicinal plants were used for the synthesis of gold nanoparticles (AuNPs) and iron nanoparticles (FeNPs). The synthesized nanoparticles were characterized by different techniques including UV-visible spectrophotometry, scanning electron microscopy (SEM), and Fourier transform infrared spectroscopy (FTIR). Furthermore, the activities of green synthesized nanoparticles were screened in vitro using, for example, antibacterial, antioxidant, cytotoxic, and DNA protection assays. Both FeNPs and AuNPs had spherical shapes with an average size less than 50 nm and were found to have good antimicrobial and nontoxic effects. Furthermore, FeNPs from Ficus microcarpa demonstrated high drug loading efficiency (65%) as compared to an anti-inflammatory drug (diclofenac potassium, DFP). We also evaluated the drug delivery potential, as well as anti-inflammatory and anticoagulant properties, of nanoparticles in vivo . Interestingly, AuNPs of Syzygium cumini exhibited strong anti-inflammatory potential as compared to DFP and diclofenac-loaded FeNPs of Ficus microcarpa . The results suggest potential pharmacological applications of biogenic synthesized AuNPs and FeNPs which can be explored further. The study revealed that the green synthesized AuNPs and FeNPs provide a promising approach for the synthesis of drug-loaded nanoparticles and consequently in the field of targeted drug delivery.